Effectiveness of Family Guidance Team (TPK) Program in Guidance in Fulfilling Toddlers' Nutrition Status in Pangkalan Lada District, West Kotawaringin Regency - Pawardani, Artika; Kuswandi, Aos; Budiati, Ayuning (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The high stunting rate in West Kotawaringin Regency, especially in Pangkalan Lada Sub-district, is the basis for this study. One of the stunting prevention programs is the Family Assistance Team, which helps families at risk of stunting. The purpose of this study is to analyze and describe the effectiveness of the Family Assistance Team (TPK) Program in assisting the fulfillment of the nutritional status of toddlers in Pangkalan Lada District. This research used a descriptive qualitative approach. For data collection, observation, interviews, and documentation were used. In this study, Budiani's theory of program effectiveness was used, which consists of four dimensions: accuracy of program targets, program socialization, program objectives, and program monitoring. The Family Assistance Team program has been effective, but has not yet reached its optimal level. Based on the research results, it shows that: 1) the accuracy of the program target has been achieved as seen from the implementation of assistance has covered all families at risk of stunting in all villages in Pangkalan Lada Subdistrict; 2) The socialization of the program has not been achieved as seen from the fact that there are still targets of the family assistance team program who have not participated in the socialization of this program; 3) the program objectives have been achieved, namely being able to reduce the prevalence from the previous year by providing assistance to fulfill child nutrition; 4) the monitoring program has been achieved through the monitoring carried out. The conclusion of this research is that the implementation of the Family Assistance Team program in Pangkalan Lada Sub-district has been effective but not optimal. Some of the obstacles encountered are the low economic income of the community and the lack of knowledge of parents about child nutrition. However, there are efforts to overcome these problems, namely through assistance to families at risk of stunting related to training, monitoring of families.